2010
DOI: 10.1149/1.3484765
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polymer Movement in Fiber Welded Cellulose Composites

Abstract: Several examples of fiber welding were characterized by visible, fluorescent, and scanning electron microscopies to evaluate polymer reorganization. Distinct morphologies were observed that are process dependent. The characterization of process controlled sample morphology is the basis for understanding observed bulk physical properties such as tensile strength and the modulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The initial work in this area has shown that by welding the loose natural fibers of the textile, a stronger textile results and that control over the properties of the textile can be adjusted by the amount of IL used to complete the welding. Trulove et al demonstrated the ability to utilize the mobility of the individual fibers to encapsulate a variety of nanomaterials within a biopolymer matrix using this technique . They showed that a catalyst could be encapsulated in a linen yarn by first coating the yarn with a catalyst ink formed from a suspension of the catalyst in the IL.…”
Section: Introductionmentioning
confidence: 99%
“…The initial work in this area has shown that by welding the loose natural fibers of the textile, a stronger textile results and that control over the properties of the textile can be adjusted by the amount of IL used to complete the welding. Trulove et al demonstrated the ability to utilize the mobility of the individual fibers to encapsulate a variety of nanomaterials within a biopolymer matrix using this technique . They showed that a catalyst could be encapsulated in a linen yarn by first coating the yarn with a catalyst ink formed from a suspension of the catalyst in the IL.…”
Section: Introductionmentioning
confidence: 99%
“…NFW is quite versatile, as any number of ILs can be applied to natural fiber materials including lignocellulose (e.g., cotton, linen, hemp, bamboo) and other biopolymers (e.g., silk, chitin). Additionally, studies have shown that NFW can maintain or improve the mechanical properties of the underlying natural fiber supports, , extending their use to more advanced engineering applications. In previous work, researchers at the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, certain ionic liquids (ILs) have been shown to be effective solvents for biopolymers such as cellulose and silk (1,2). Very recently, "natural fiber welding", the selective mobilization and restructuring of biopolymers to create functionalized composite materials, has been demonstrated (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Fiber welding techniques entail the utilization of IL-based solvents to partially solubilize and mobilize biopolymers in (fibrous) natural material substrates.…”
Section: Introductionmentioning
confidence: 99%